AI in Medicine: A Transformative Force in Modern Healthcare - Vallas, Angelos; Stamatiou, Marianna; Tsaila , Matina; Filippousi, Raia (Open Schools Journal for Open Science, 2025)
Artificial Intelligence (AI) is transforming modern medicine by revolutionizing how treatments are designed, how diseases are diagnosed, and how patients are managed. From personalized medicine to robotic surgery, AI’s impact is evident across various domains, contributing to improved outcomes and efficiency in healthcare systems.